2014
DOI: 10.1371/journal.pone.0108484
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeepers or Intermediaries? The Role of Clinicians in Commercial Genomic Testing

Abstract: BackgroundMany commentators on “direct-to-consumer” genetic risk information have raised concerns that giving results to individuals with insufficient knowledge and training in genomics may harm consumers, the health care system, and society. In response, several commercial laboratories offering genomic risk profiling have shifted to more traditional “direct-to-provider” (DTP) marketing strategies, repositioning clinicians as the intended recipients of advertising of laboratory services and as gatekeepers to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…In one study of interviews conducted with clinicians who offered genomic-risk assessment to patients, the clinicians appeared to have learned most of what they know about genomics directly from the commercial laboratories. 36 In the absence of professional counseling and interpretation, there are concerns that consumers might make misguided changes in their health care or lifestyle. 37 Fortunately, empiric studies of DTC GT to date have shown little or no evidence of inappropriate changes in lifestyle or health-related behaviors.…”
Section: Direct-to-consumer Testingmentioning
confidence: 99%
“…In one study of interviews conducted with clinicians who offered genomic-risk assessment to patients, the clinicians appeared to have learned most of what they know about genomics directly from the commercial laboratories. 36 In the absence of professional counseling and interpretation, there are concerns that consumers might make misguided changes in their health care or lifestyle. 37 Fortunately, empiric studies of DTC GT to date have shown little or no evidence of inappropriate changes in lifestyle or health-related behaviors.…”
Section: Direct-to-consumer Testingmentioning
confidence: 99%
“…Thus, many HPs have no choice but to rely on the testing companies for training and support. Already, interviews with North American HPs who facilitated health‐related PGT with their patients revealed that most relied heavily upon testing company resources to counsel their patients . As with HPs using testing company information for their own websites, this reliance represents a conflict of interest, such that clients may receive biased or inadequate advice.…”
Section: Discussionmentioning
confidence: 99%
“…As Parker and colleagues have also suggested [15], bolstering the attendance and engagement of professionals from medical genetics and pharmacology are especially warranted to increase substantive expertise and understanding of genetics and drug pathways. The potential for dependence on commercial laboratory interpretation of test results poses a problem for the rapid integration of un(der)-validated genomic tests, posing risks to the integrity of clinical judgment and patient care [5]. This may be especially important if the MGTB is to avoid overreliance on the commercial laboratory’s interpretation of genomic test results, a concern raised both by physician-scientists and basic scientists who noted the group’s relatively uncritical acceptance of the validity of (FoundationOne TM ) results.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the rapid integration of genomic tests [4], care paths for using test results to guide treatment do not yet exist. Given concerns regarding insurance coverage and cost effectiveness of genomic testing and uncertain ethical implications of genomic information, establishing protocols for administering and delivering genomic risk information to patients is important [2, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%